Lactate activation of α-cell KATP channels inhibits glucagon secretion by hyperpolarizing the membrane potential and reducing Ca2+ entry - Karolina E. Zaborska; Prasanna K. Dadi; Matthew T. Dickerson; Arya Y. Nakhe; Ariel S. Thorson; Charles M. Schaub; Sarah M. Graff; Jade E. Stanley; Roy S. Kondapavuluru; Jerod S. Denton; David A. Jacobson (Elsevier, 2020)
Objective: Elevations in pancreatic α-cell intracellular Ca2+ ([Ca2+]i) lead to glucagon (GCG) secretion. Although glucose inhibits GCG secretion, how lactate and pyruvate control α-cell Ca2+ handling is unknown. Lactate enters cells through monocarboxylate transporters (MCTs) and is also produced during glycolysis by lactate dehydrogenase A (LDHA), an enzyme expressed in α-cells. As lactate activates ATP-sensitive K+ (KATP) channels in cardiomyocytes, lactate may also modulate α-cell KATP. Therefore, this study investigated how lactate signaling controls α-cell Ca2+ handling and GCG secretion. Methods: Mouse and human islets were used in combination with confocal microscopy, electrophysiology, GCG immunoassays, and fluorescent thallium flux assays to assess α-cell Ca2+ handling, Vm, KATP currents, and GCG secretion. Results: Lactate-inhibited mouse (75 ± 25%) and human (47 ± 9%) α-cell [Ca2+]i fluctuations only under low-glucose conditions (1 mM) but had no effect on β- or δ-cells [Ca2+]i. Glyburide inhibition of KATP channels restored α-cell [Ca2+]i fluctuations in the presence of lactate. Lactate transport into α-cells via MCTs hyperpolarized mouse (14 ± 1 mV) and human (12 ± 1 mV) α-cell Vm and activated KATP channels. Interestingly, pyruvate showed a similar KATP activation profile and α-cell [Ca2+]i inhibition as lactate. Lactate-induced inhibition of α-cell [Ca2+]i influx resulted in reduced GCG secretion in mouse (62 ± 6%) and human (43 ± 13%) islets. Conclusions: These data demonstrate for the first time that lactate entry into α-cells through MCTs results in KATP activation, Vm hyperpolarization, reduced [Ca2+]i, and inhibition of GCG secretion. Thus, taken together, these data indicate that lactate either within α-cells and/or elevated in serum could serve as important modulators of α-cell function.